2020
DOI: 10.1097/mph.0000000000001880
|View full text |Cite
|
Sign up to set email alerts
|

Clinicoepidemiologic Profile and Outcome Predicted by Minimal Residual Disease in Children With Mixed-phenotype Acute Leukemia Treated on a Modified MCP-841 Protocol at a Tertiary Cancer Institute in India

Abstract: Introduction: Mixed-phenotype acute leukemia (MPAL) accounts for 1.2% to 5% of acute leukemia across age groups with intermediate prognosis. We evaluated clinicoepidemiologic profiles and outcomes of MPAL. Methods: Records of children younger than 15 years of age with acute leukemia from January 2010 to December 2016 were reviewed on the basis of the MPAL WHO 2008 criteria. Treatment was uniform with a modified MCP-841 protocol. Descriptive analysis too… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 19 publications
1
5
0
Order By: Relevance
“…With little data available on this rare subtype of acute leukemias, the authors report on a series of 42 children treated for MPAL, achieving a 5-year event-free survival (EFS) of 56% and overall survival (OS) of 61%. These results are comparable to data from two pediatric MPAL series in India, highlighting the challenges in managing high-risk pediatric leukemias in resource-limited settings ( 5 , 6 ). In one of the largest reports of pediatric MPALs from LMICs, the authors highlight the difficulties of treating high-risk pediatric leukemia in resource-limited settings.…”
supporting
confidence: 74%
See 1 more Smart Citation
“…With little data available on this rare subtype of acute leukemias, the authors report on a series of 42 children treated for MPAL, achieving a 5-year event-free survival (EFS) of 56% and overall survival (OS) of 61%. These results are comparable to data from two pediatric MPAL series in India, highlighting the challenges in managing high-risk pediatric leukemias in resource-limited settings ( 5 , 6 ). In one of the largest reports of pediatric MPALs from LMICs, the authors highlight the difficulties of treating high-risk pediatric leukemia in resource-limited settings.…”
supporting
confidence: 74%
“…from Egypt discuss the challenges in managing mixed-phenotype acute leukemia (MPAL) in LMICs. MPAL is a relatively rarer subtype of acute leukemias, and there are limited data, especially on children from LMICs ( 5 , 6 ). With little data available on this rare subtype of acute leukemias, the authors report on a series of 42 children treated for MPAL, achieving a 5-year event-free survival (EFS) of 56% and overall survival (OS) of 61%.…”
mentioning
confidence: 99%
“…Treatment is largely guided by MRD and bone marrow transplant is reserved for those with inadequate response to therapy 5,9 . Previous studies have shown non‐inferior outcomes in both CD19 + and CD19 − cases compared to non‐ALAL cases with MRD 0·1% or higher after induction treated on current intensified protocols 5,12,13 …”
Section: Patient Age Years Gender Diagnosis Presenting Wbc ×109/l Imm...mentioning
confidence: 99%
“…5 Treatment is largely guided by MRD and bone marrow transplant is reserved for those with inadequate response to therapy. 5,9 Previous studies have shown non-inferior outcomes in both CD19 + and CD19 À cases compared to non-ALAL cases with MRD 0Á1% or higher after induction treated on current intensified protocols. 5,12,13 We conducted a multicentre retrospective study with chart and pathology review of all cases of MPAL/ALAL diagnosed and treated at University Hospital Southampton (UHS) and Sheffield Children's Hospital (SCH), UK from the year 2015 until 2020.…”
mentioning
confidence: 99%
See 1 more Smart Citation